Talkitt: toward a new instrument based on artificial intelligence for augmentative and alternative communication in children with down syndrome - Costanzo, Floriana; Fucà, Elisa; Caciolo, Cristina; Ruà, Deborah; Smolley, Sara; Weissberg, Danny; Vicari, Stefano (Frontiers in Psychology, 2023)
Introduction Individuals with Down syndrome (DS) often exhibit a severe speech impairment, with important consequences on language intelligibility. For these cases, the use of Augmentative Alternative Communication instruments, that increase an individual’s communication abilities, becomes crucial. Talkitt is a mobile application created by Voiceitt Company, exploiting speech recognition technology and artificial intelligence models to translate in real-time unintelligible sounds into clear words, allowing individuals with language production impairment to verbally communicate in real-time. Methods The study evaluated the usability and satisfaction related to the Talkitt application use, as well as effects on adapted behavior and communication, of participants with DS. A final number of 23 individuals with DS, aged 5.54 to 28.9 years, participated in this study and completed 6 months of training. The application was trained to consistently recognize at least 20 different unintelligible words (e.g., nouns and/or short phrases)/person. Results Results revealed good usability and high levels of satisfaction related to the application use. Moreover, we registered improvement in linguistic abilities, particularly naming. Discussion These results paves the road for a potential role of Talkitt application as a supportive and rehabilitative tool for DS.